2000
DOI: 10.1073/pnas.97.12.6334
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutations and suppressors affecting interactions between the subunits of the HIV type 1 reverse transcriptase

Abstract: HIV-1 reverse transcriptase (RT) catalyzes the conversion of genomic RNA into cDNA. The enzyme is a heterodimer of p66 and p51 subunits, and the dimerization of these subunits is required for optimal enzyme activity. To analyze this process at the genetic level, we developed constructs that permit the detection of the interaction between these subunits in the yeast two-hybrid system. Genetic analysis of RT subdomains required for heterodimerization revealed that the fingers and palm of p66 were dispensable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 39 publications
2
76
0
2
Order By: Relevance
“…Past studies have confirmed that most amino acid substitution mutations in RT do not significantly impact PR-mediated Gag cleavage, regardless of whether or not they affect RT dimerization. Substitution mutations at the RT primer grip residues L234, W239, and W229 (6,16,25,43,50) or at the tryptophan repeat motif residues W401 and W414 (44) that abrogate RT dimerization in vitro are not associated with impaired Gag processing and/or virion production, even though the L234D and W239A mutants are both deficient in virusassociated RT-presumably due (at least in part) to premature Gag-Pol cleavage (25,49,51). Furthermore, substitution mutations at HIV-1 RT G191 that are capable of facilitating RT dimerization in vitro (15) have no significant impact on virus particle assembly and release (23).…”
Section: Resultsmentioning
confidence: 99%
“…Past studies have confirmed that most amino acid substitution mutations in RT do not significantly impact PR-mediated Gag cleavage, regardless of whether or not they affect RT dimerization. Substitution mutations at the RT primer grip residues L234, W239, and W229 (6,16,25,43,50) or at the tryptophan repeat motif residues W401 and W414 (44) that abrogate RT dimerization in vitro are not associated with impaired Gag processing and/or virion production, even though the L234D and W239A mutants are both deficient in virusassociated RT-presumably due (at least in part) to premature Gag-Pol cleavage (25,49,51). Furthermore, substitution mutations at HIV-1 RT G191 that are capable of facilitating RT dimerization in vitro (15) have no significant impact on virus particle assembly and release (23).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is very likely that the domains responsible for RT incorporation into VLPs exist between RT residues 183 and 305. Some mutations in this region have been shown to block p66/p51 heterodimer formation (49). It remains to be determined if the truncation mutations affect RT dimerization and consequently diminish RT incorporation into VLPs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown enhancement of the homodimerization of RT and PR-RT fragments by EFV in yeast two-hybrid assays (27,28,30). We initially used yeast two-hybrid assay systems with pAD-GAL4 and pBD-GAL4 plasmids (Stratagene) but did not see detectable levels of RT expression (data not shown), as suggested previously (61). As an alternative method, we employed a bacterial two-hybrid assay with pBT and pTRG plasmids (Stratagene) (Fig.…”
Section: Efficient Dimerization Of Pr-rt Is Further Enhanced By Efv mentioning
confidence: 99%